User Interactivity for Text Visualization System - Samaiya, Shashak; Jain, Yastika; Jain, Priyanka (International Journal of Computer Sciences and Engineering, 2025)
This paper outlines the long-term vision to automate a language-less visualization system for communication with minimum language dependency. It proposes an interactive approach for Preksha, as Hindi text visualizer. Preksha is the process of understanding a natural language, transform the knowledge into a language independent abstract form and rendering a 3D Scene for visualization. Considering linguistic nature as morphologically rich and free-word-order for ‘Hindi’ language, the proposed work offers an approach for user interaction with system, in case of requirement.